Assessment of Saponification, Acid, Peroxide, and Iodine Values by Physicochemical Analysis of Reused Cooking Oil - Lie huan zang (AKADEMI SERTIFIKASI PROFESI INTERNASIONAL, 2025)
This study examines the deterioration of frying oils utilised in local food enterprises by analysing essential quality indicators. Oil samples, obtained after extended frying of typical food items like samosas, Manchurian, chicken, medu vada, jalebi, and momos for durations of 8 to 9 hours, were analysed. Palm and vegetable oils were evaluated for acid value, saponification value, peroxide value, and iodine value utilising standard titrimetric methods. Acid-base titration techniques were employed to determine acid, peroxide, and saponification levels, whereas iodometric titration was utilised for assessing iodine value. The comparative analysis underscores the chemical alterations in reused oils, stressing the importance of consistent monitoring to guarantee safety and appropriateness for ongoing usage in food preparation